Data-Based Self-awareness as the Foundation for Effective Leadership. (October 2021) - Friedman, Alan; Hancock, Beverly; Thompson, Pamela Austin
Abstract : The AONL Nurse Executive Fellowship supports nurses who are new to an executive role in developing critical executive competencies. Participants engage in an in-depth specialized assessment process to help them understand themselves and the impact on their leadership. Learnings from the 1st 2 cohorts of fellowship participants provide insight into challenges faced by new executives and how self-awareness can improve performance to address those challenges.